1999
DOI: 10.1111/j.1749-6632.1999.tb08018.x
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channel Modulation as the Basis for Neuroprotective Action of MS‐153

Abstract: MS-153, (R)-(-)-5-methyl-1-nicotinoyl-2-pyrazoline, is a new neuroprotective drug. Recent data in the literature suggest that it inhibits glutamate accumulation occurring during ischemia and the translocation of protein kinase C gamma (PKC gamma). The present study was undertaken to prove the hypothesis that MS-153 blocks neuroreceptors and ion channels involved in glutamate accumulation. Neurons isolated from rat dorsal root ganglia and frontal cortex were used for recording channel currents by the whole-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…MS-153 can block voltage-gated calcium channels through a mechanism that is protein kinase C (PKC)-dependent 46 ; MS-153 inhibits the translocation and activation of PKC-c that leads to the suppression of the calcium channel current. 45 Calcium channel blockers such as emopamil 79 and nimodipine 80 have been shown to be neuroprotective in TBI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MS-153 can block voltage-gated calcium channels through a mechanism that is protein kinase C (PKC)-dependent 46 ; MS-153 inhibits the translocation and activation of PKC-c that leads to the suppression of the calcium channel current. 45 Calcium channel blockers such as emopamil 79 and nimodipine 80 have been shown to be neuroprotective in TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the decrease in calpain-mediated spectrin proteolysis would suggest that the effects of MS-153 are mediated via a reduction of calcium influx into injured cells. 46 Several classes of compounds including NMDA receptor antagonists 81 and compounds that target calcium influx, 79,82 have been shown to ameliorate cellular damage and neurologic deficits, as well as cognitive decline and motor impairments caused by TBI. In models of brain injury, glutamate receptor antagonists, such as kynurenate, 83 NBQX, and CGS 19755, 84 have been reported to partially ameliorate cytoskeletal injury with preserved immuno-labeling of MAP-2 and to reduce the accumulation of calpain-cleaved spectrin byproducts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Although the exact mechanism(s) by which MS-153 exerts its neuroprotective effects is-A C H T U N G T R E N N U N G (are) not entirely understood, it has been suggested that it inhibits high voltage-gated calcium channels, thereby inhibiting release of glutamate from nerve terminals in ischemic conditions. [6] Due to this intriguing activity we decided to undertake an investigation geared towards an efficient asymmetric synthesis of MS-153.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Although the exact mechanism(s) by which MS-153 exerts its neuroprotective effects is-A C H T U N G T R E N N U N G (are) not entirely understood, it has been suggested that it inhibits high voltage-gated calcium channels, thereby inhibiting release of glutamate from nerve terminals in ischemic conditions. [6] Due to this intriguing activity we decided to undertake an investigation geared towards an efficient asymmetric synthesis of MS-153. Due to its relatively simple structure we set at the outset several boundary conditions for the synthesis including only a very small number of operationally trivial, inexpensive, and environmentally benign steps that all proceed with excellent efficiency and, where relevant, near-perfect enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%